2012
DOI: 10.1097/pcc.0b013e31823c980f
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of sepsis in pediatric intensive care units

Abstract: Sepsis is common in Colombian pediatric intensive care units. Clear risk factors for getting sick and dying from this disease were identified. Mortality resulting from this disease is considerable for a developing society like ours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
1
21

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 36 publications
2
76
1
21
Order By: Relevance
“…The mortality in the present study also reflects the high rate of multiorgan dysfunction. In previous studies, investigators have reported 19-57% mortality for pediatric patients with sepsisassociated MODS (2,3,48). Thus, the mortality reported in our present study is indicative of the critically ill subset of children with sepsis-associated MODS who should be targeted for enrollment into interventional trials.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…The mortality in the present study also reflects the high rate of multiorgan dysfunction. In previous studies, investigators have reported 19-57% mortality for pediatric patients with sepsisassociated MODS (2,3,48). Thus, the mortality reported in our present study is indicative of the critically ill subset of children with sepsis-associated MODS who should be targeted for enrollment into interventional trials.…”
Section: Discussionmentioning
confidence: 65%
“…However, these studies used International Classification of Diseases, Ninth Revision (ICD-9), codes, which have been shown to capture a lower severity of illness and thereby underestimate mortality (5,7). In a recent database study using expanded ICD-9 coding, researchers reported a PICU mortality of 26.4% (6), and authors of prospective studies have reported short-term mortality rates up to 24% (2,5,19,46,47). The mortality in the present study also reflects the high rate of multiorgan dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Local epidemiologic studies about pediatric sepsis have been undertaken, most of them in developed countries. However, the important differences between children in developing countries and those in developing ones are clear [8].…”
Section: Introductionmentioning
confidence: 99%